Export dynamics and sales at home - Nicolas Berman; Antoine Berthou; Jérôme Héricourt (European Central Bank (ECB), 2014)
Using a French firm-level database that combines balance-sheet and product-destination-specific export information over the period 1995-2001, we study the interconnections between exports and domestic sales. We identify exogenous shocks that affect the firms' demand on foreign markets to instrument yearly variations in exports. We use alternatively as instruments product-destination specific imports or tariffs changes, and large foreign shocks such as financial crises or civil wars. Our results show that exogenous variations in foreign sales are positively associated with domestic sales, even after controlling for changes in domestic demand. A 10% exogenous increase in exports generates a 1 to 3% increase in domestic sales in the short-term. This result is robust to various estimation techniques, instruments, controls, and sub-samples. We provide empirical evidence suggesting that this positive effect of exogenous changes in exports on domestic sales is related to a relaxation of short-run liquidity constraints.
Keywords: F10; F44; L20; 330; demand shocks; domestic sales; export dynamics; liquidity; markets